POLA PEWARISAN KARAKTER KUALITATIF KACANG PANJANG (VIGNA SINENSIS VAR. SESQUIPEDALIS L.) KETURUNAN TESTA COKLAT X HITAM - Sriwidarti, Sriwidarti; Sa?diyah, Nyimas; Utomo, Setyo Dwi; Barmawi, Maimun (JURNAL AGROTROPIKA, 2010)
Experiments were conducted at farm area Gedung Pakuon village?s Kecamatan Baradatu Kabupaten Way Kanan ? Lampung and the Laboratory of Seed of Lampung University, on April 2009 to Januari 2010. In the first experiment used P1 (brown/C), P2 (black), dan F1 (C x H), to have seed for planted on the second experiment. In the second experiment the population of P1 (coklat), P2 (hitam), F1 (C x H), F1 resiprok (H x C), BC1 (F1 x C), BC2(F1 x H), dan F2. Were tested to estimasi number of controlling gen, gene action, and maternall effect. The character were observed i.e. the colour of seed skin and the colour of pods. The result showed that F2 population in the colour of pods were not normal distribution, and base on estimated number of gen this character was controlled by 2 genes with inheritance controlled by a simple gen. Inheritance pattern of the colour of seed skin have complex equivalent, and segregation in F2 population. The colour of pods with mendelian ratio of 12:3:1 (dark green : green : bright green). Result of experiment to maternal effect indicated that there was maternal effect in the the colour of seed skin, but not in the colour of pods.Key Words: yardlong bean, maternall effect, heritability